2017
DOI: 10.1021/acsnano.7b00370
|View full text |Cite
|
Sign up to set email alerts
|

Smart Contact Lenses with Graphene Coating for Electromagnetic Interference Shielding and Dehydration Protection

Abstract: Recently, smart contact lenses with electronic circuits have been proposed for various sensor and display applications where the use of flexible and biologically stable electrode materials is essential. Graphene is an atomically thin carbon material with a two-dimensional hexagonal lattice that shows outstanding electrical and mechanical properties as well as excellent biocompatibility. In addition, graphene is capable of protecting eyes from electromagnectic (EM) waves that may cause eye diseases such as cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
141
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(143 citation statements)
references
References 28 publications
1
141
0
1
Order By: Relevance
“…Precise location and tailoring at the atomic scale of 2D materials are able to tune the physical properties. Although there are diverse preparation methods, high‐precision and large‐scale processing method is always a challenge . Here, we take some methods as examples, including bottom‐up fabrication such as self‐assembly, plasma enhanced chemical vapor deposition (CVD) and site‐selective growth, as well as top‐down fabrication such as helium ion beam technology, nanoimprint lithography, inkjet printing, screen printing, electron beam lithography, and nanosphere lithography, as shown in Figure …”
Section: Fabrication Of Patterned 2d Materialsmentioning
confidence: 99%
“…Precise location and tailoring at the atomic scale of 2D materials are able to tune the physical properties. Although there are diverse preparation methods, high‐precision and large‐scale processing method is always a challenge . Here, we take some methods as examples, including bottom‐up fabrication such as self‐assembly, plasma enhanced chemical vapor deposition (CVD) and site‐selective growth, as well as top‐down fabrication such as helium ion beam technology, nanoimprint lithography, inkjet printing, screen printing, electron beam lithography, and nanosphere lithography, as shown in Figure …”
Section: Fabrication Of Patterned 2d Materialsmentioning
confidence: 99%
“…In 2014, Google demonstrated a proof‐of‐concept electrical contact lens that assists diabetics by monitoring the glucose level in their tears and transferring related information wirelessly if the glucose concentration remains high after the wearer has eaten a meal . Other research efforts include a readout integrated circuit (IC) chip for wireless communication from a contact lens, a graphene lens coating for electromagnetic interference shielding, and sensors to monitor intraocular pressure and biochemical changes for human diagnostics. Separately, Minteer and co‐workers developed chemical sensors and biofuel cell systems on contact lenses.…”
Section: Introductionmentioning
confidence: 99%
“…While these studies demonstrated proof‐of‐concept sensing platforms, the correlation of blood glucose and tear glucose has not been clearly established . Other studies involved coating contact lenses with graphene to reduce electromagnetic field interference and induce dehydration protection …”
Section: Introductionmentioning
confidence: 99%